2007
DOI: 10.1021/jf071069u
|View full text |Cite
|
Sign up to set email alerts
|

Free Hydroxycinnamic Acids, Lycopene, and Color Parameters in Tomato Cultivars

Abstract: Concentrations of antioxidant compounds (total phenolic compounds, free hydroxycinnamic acids, and lycopene) and color parameters ( a*, b*, and L*) were determined in 167 tomato samples belonging to five cultivars (Dorothy, Boludo, Dunkan, Dominique, and Thomas) produced on the island of Tenerife. Chlorogenic, caffeic, p-coumaric, and ferulic acids were identified and quantified in the tomato samples. Chlorogenic acid had the highest mean concentration, whereas the p-coumaric was not detected in almost half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
(117 reference statements)
4
33
6
Order By: Relevance
“…An aliquot of 10.0±1.0 g was placed in an ashing dish and then in a hot sand bath until complete sample carbonization. After carbonization, samples were placed in a Gallenkamp furnace (Loughborough, UK) at 550±10°C for 24 h until complete incineration (AOAC 1990;Hernández et al 2005).…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…An aliquot of 10.0±1.0 g was placed in an ashing dish and then in a hot sand bath until complete sample carbonization. After carbonization, samples were placed in a Gallenkamp furnace (Loughborough, UK) at 550±10°C for 24 h until complete incineration (AOAC 1990;Hernández et al 2005).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Appropriate water dilutions were made for Na and K determination. The wavelength and curve range conditions used are shown in Table 3 (AOAC 1990;Hernández et al 2005).…”
Section: Assessment Of Mineral Contents In Tomato Fruitsmentioning
confidence: 99%
“…Moreover, it is widely recognized that the protective role of tomato consumption is due to the synergistic effect among the different classes of antioxidants. Aside from the genetic potential of the cultivar, agronomic and environmental conditions, ripening stage of fruit and post-harvest storage are known to affect the chemical composition of tomatoes (Garcia and Barrett, 2006;Hernández et al, 2007; AlSanabani et al, (2013). Adejumo (2012) reported that a medium sized tomato contributes 40% of ascorbic acid (vitamin C) required in humans, which is important in forming collagen, a protein that gives structure to the bones, cartilage, muscle, and blood vessels and aids in the absorption of iron.…”
mentioning
confidence: 99%
“…Some researchers reported that an accumulation of secondary plant compounds in tomatoes can be triggered by elevated daily mean temperatures ranging between 18.5 °C and 26 °C (Krumbein et al 2006;Toor et al 2006), which could be the reason for increasing contents of valuable plant compounds in the present study. Otherwise, Hernandez et al (2007) analyzed the lycopene content in tomatoes on a monthly basis from October to June. By using the recorded data in this study, it can be calculated that the accumulation of lycopene decrease with decreasing RH ranging between 70 % and 55 %.…”
Section: Resultsmentioning
confidence: 99%